Dental trauma and oral health-related quality of life among 7th-grade students of public elementary schools1 - Catananti, Isabella Silva [UNESP]; de Abreu-e-Lima, Fabio Cesar Braga [UNESP]; da Silva, Silvio Rocha Corrêa [UNESP]; Pardi, Vanessa; da Silva Tagliaferro, Elaine Pereira [UNESP] (Universidade Estadual de Campinas, 2023)
Dental trauma is a public health problem because of its high prevalence rates and treatment costs and for affecting mainly younger individuals. Aim: This cross-sectional study aimed to investigate the variables associated with dental trauma and its influence on oral health-related quality of life among 7th-grade students of public elementary schools. Methods: The data was collected with semi-structured and self-administered questionnaires and an intraoral clinical examination (n = 204). The variables collected regarded dental trauma, lip coverage, overjet, oral health-related quality of life (Child Perceptions Questionnaire - CPQ11-14 ISF: 8), and sociodemographic profile. Association tests and the Mann-Whitney test were performed at a 5% significance level. Results: Dental trauma occurred in 12.3% of students, 94.6% had adequate lip coverage, and the mean overjet was 2.7 mm (±2.0). Sex was the only variable with a statistically significant association with dental trauma (p = 0.021). There was no statistically significant difference in the CPQ11-14 ISF: 8 score between students with and without dental trauma (p = 0.136). Conclusions: Dental trauma was significantly associated with sex and did not impact the oral health-related quality of life of the students.
Keywords: Oral health; Quality of life; Tooth fractures; Tooth injuries